2014
DOI: 10.1111/hiv.12171
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of chloroquine as a modulator of immune activation to improve CD4 recovery in immune nonresponding HIV‐infected patients receiving antiretroviral therapy

Abstract: ObjectivesChloroquine (CQ), an anti-inflammatory drug, inhibits Toll-like receptor (TLR) signalling in plasmacytoid dendritic cells (pDCs) and may be beneficial for HIV-infected patients in whom immune activation persists despite effective antiretroviral therapy (ART). The effect of CQ on CD4 T-cell recovery and immune activation in immune nonresponding patients receiving successful ART was therefore studied. MethodsNineteen adults on ART with CD4 counts ≤350 cells/μL and undetectable viral load (VL) orally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 37 publications
0
42
0
Order By: Relevance
“…Together, however, these data suggest that altering the microbiome may reduce chronic inflammation but whether this translates into cardiovascular benefit remains undetermined. Quinolines such as chloroquine and hydroxychloroquine have also been tested in patients with HIV with inconclusive results regarding effects on microbial translocation and inflammation [151155], possibly due to differences in the dose of medication used or whether patients were treated with cART. Recent studies with these two medications are either ongoing or have yet to publish final results (NCT01232660 and NCT00819390).…”
Section: Novel Use Of Interventions To Reduce Immune Activation and Cmentioning
confidence: 99%
“…Together, however, these data suggest that altering the microbiome may reduce chronic inflammation but whether this translates into cardiovascular benefit remains undetermined. Quinolines such as chloroquine and hydroxychloroquine have also been tested in patients with HIV with inconclusive results regarding effects on microbial translocation and inflammation [151155], possibly due to differences in the dose of medication used or whether patients were treated with cART. Recent studies with these two medications are either ongoing or have yet to publish final results (NCT01232660 and NCT00819390).…”
Section: Novel Use Of Interventions To Reduce Immune Activation and Cmentioning
confidence: 99%
“…In some studies this molecule was shown to reduce immune activation markers (i.e., IL-6, TNF-a and LPS) and CD8 T-cells expressing CD38CHLA-DRC and Ki-67, 158-161 while other researchers found no effect on immune-activation. [162][163][164] A possible target is also represented by TNF itself, which may be antagonized by several molecules currently in use for rheumatologic diseases. A study in rhesus macaques showed that adalimumab, a human anti-TNF monoclonal antibody, was able to reduce infiltration of polymorphonuclear cells into the T-cell zone of lymphoid tissues, diminishing also lymphoid tissue fibrosis; nevertheless, no effect on plasma immune activation was proven.…”
Section: New Treatment Strategies and Immunotherapy In Aging Hiv Patimentioning
confidence: 99%
“…Another open question is why it is that strategies to reduce T cell activation offer little or no benefit as adjuncts to ART, e.g., cyclosporine A (99), corticosteroids (100), mycophenylate motefil (101), chloroquine (102), or even recombinant IL-2 (103), which is known to antagonize the generation of Tfh (104). …”
Section: Expanded Hiv-1 Dna-infected Tfh As a Barrier To A Curementioning
confidence: 99%